An evaluation of emerging vaccines for childhood pneumococcal pneumonia - Webster, Julia; Theodoratou, Evropi; Nair, Harish; Seong, Ang Choon; Zgaga, Lina; Huda, Tanvir; Johnson, Hope L; Madhi, Shabir; Rubens, Craig; Zhang, Jian Shayne F; El Arifeen, Shams; Krause, Ryoko; et al. (BMC public health, 2011)
Background Pneumonia is the leading cause of child mortality worldwide. Streptococcus pneumoniae (SP) or pneumococcus is estimated to cause 821,000 child deaths each year. It has over 90 serotypes, of which 7 to 13 serotypes are included in current formulations of pneumococcal conjugate vaccines that are efficacious in young children. To further reduce the burden from SP pneumonia, a vaccine is required that could protect children from a greater diversity of serotypes. Two different types of vaccines against pneumococcal pneumonia are currently at varying stages of development: a multivalent pneumococcal conjugate vaccine covering additional SP serotypes; and a conserved common pneumococcal protein antigen (PPA) vaccine offering protection for all serotypes. Methods We used a modified CHNRI methodology for setting priorities in health research investments. This was done in two stages. In Stage I, we systematically reviewed the literature related to emerging SP vaccines relevant to several criteria of interest: answerability; efficacy and effectiveness; cost of development, production and implementation; deliverability, affordability and sustainability; maximum potential for disease burden reduction; acceptability to the end users and health workers; and effect on equity. In Stage II, we conducted an expert opinion exercise by inviting 20 experts (leading basic scientists, international public health researchers, international policy makers and representatives of pharmaceutical companies). The policy makers and industry representatives accepted our invitation on the condition of anonymity, due to sensitive nature of their involvement in such exercises. They answered questions from CHNRI framework and their “collective optimism” towards each criterion was documented on a scale from 0 to 100%. Results The experts expressed very high level of optimism (over 80%) that low-cost polysaccharide conjugate SP vaccines would satisfy each of the 9 relevant CHNRI criteria. The median potential effectiveness of conjugate SP vaccines in reduction of overall childhood pneumonia mortality was predicted to be about 25% (interquartile range 20-38%, min. 15%, max 45%). For low cost, cross-protective common protein vaccines for SP the experts expressed concerns over answerability (72%) and the level of development costs (50%), while the scores for all other criteria were over 80%. The median potential effectiveness of common protein vaccines in reduction of overall childhood pneumonia mortality was predicted to be about 30% (interquartile range 26-40%, min. 20%, max 45%). Conclusions Improved SP vaccines are a very promising investment that could substantially contribute to reduction of child mortality world-wide.